ROLE OF CYCLIN D1 IN THE MECHANISMS OF TAMOXIFEN RESISTANCE - D. B. Erdyneeva (Sibirskij Onkologičeskij Žurnal, 2020)
Hormone-receptor positive breast cancer is the most common molecular subtype and represents 60–75 % of all breast cancers (BC). The presence of specific molecular targets such as the estrogen/progesterone receptor determines the use of hormone therapy for patients with this subtype. Tamoxifen, a selective estrogen receptor modulator, remains the first adjuvant treatment choice for the hormone-receptor positive BC patients. However, tamoxifen resistance is the major limitation of its efficacy. In this regard, the study of drug resistance mechanisms as well as search for biological prognostic markers of tamoxifen efficacy is very important. Cyclin D1 is a representative of the regulatory protein family, which plays a central role in the cell cycle regulation. The data on the association between cyclin D1 and estrogen-dependent signaling as well as the characteristics of CCND1 gene and its most studied polymorphic loci, were presented. The prognostic significance of cyclin D1 in hormone-receptor positive BC receptor-positive breast cancer was described. The experimental and clinical studies data on the association between the cyclin D1 expression level and tamoxifen efficacy are analyzed. Current approaches to overcoming hormone resistance based on cyclin D1 studies were considered.